Mining Instruction From Student Mistakes: Conducting an Error Analysis for Mathematical Problem Solving. (December 2020) - Peltier, Corey; Peltier, Tiffany K.
The mathematics performance of students identified with emotional and behavioral disorders (EBD) is poor. Students identified with EBD require individualized instruction aligned with their unique academic and behavioral needs. One way that teachers can efficiently identify core mathematics deficits and provide individualized instruction is through the effective use of error analysis. In this article, we describe how error analysis can be used to individualize mathematics instruction for students with EBD, providing a case scenario as an exemplar.